The Effectiveness of Virgin Coconut Oil (VCO) and Red Betel Leaf Infusion on The Healing Time of Second-Degree Perineal Lacerations in Postpartum - Musdalifah, Ulfah; Aisyah, Luthfia Nur; Rosiana, Heny; Yuniarti, Yuniarti (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2024)
The cause of infection in postpartum women is due to the perineal wound. Data released from Purbalingga district health office in 2022, Kutawis Health Center ranked second in the incidence of perineal wound infection. Virgin Coconut Oil (VCO) and red betel leaf are known contains chemicals that are antiseptic and antibacterial. The purpose of this study was to determine the effectiveness of VCO and red betel leaf water decoction on the healing time of perineal lacerations of grade II postpartum women in the Kutawis Health Center working area of Purbalingga Regency. This type of research uses quasy experimental design, two group pretest posttest design. The sample of this study are 34 people taken using accidental sampling. The sample was divided into 2 groups. Data analysis using Mann Whitney test. The results of the intervention group obtained p value <0.025. (p-value <0.05). It can be concluded that there is a significant difference between groups using VCO and red betel leaf water decoction. An average wound healing using VCO 6.17 days and the group using red betel leaf decoction on average healed 5.58 days. Based on the research, it is known that there is a difference in the healing time of perineal wounds between treatments using VCO and red betel leaf water decoction. Treatment using red betel leaf is faster wound healing than treatment using VCO. From the results of this study it is hoped that it can be applied independently so that it can accelerate the healing of lacerations.